Distribusi Jenis Asing Invasif Melothria pendula L. (Cucurbitaceae) di Kawasan Konservasi Ilmiah Kebun Raya Bogor - Kekung, Cristina Mega Meyfiani; Husaini, Iin Pertiwi A; Turhadi, Turhadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Melothria pendula is belong to Cucurbitaceae family and originates from America continent. Previous research reported findings of M. pendula in several regions in Indonesia, such as in Bogor Botanical Gardens (KRB) as invasive species. The appearance of M. pendula in KRB has not yet been inventoried. As invasive species, M. pendula has the potential to be a threat to collection and native plants. This research aims to report the distribution of M. pendula in the scientific conservation area of KRB and measure the abiotic factors in the locations where M. pendula was found. This research was exploratory method which was carried out by exploring and morphological characterization of M. pendula. Measurement of abiotic factors, including temperature, air humidity, light intensity, and wind speed at each site where M. pendula was found. QGIS is used to mapping the distribution of M. pendula. Based on this study showed that there were 40 individuals of M. pendula which found distributed randomly in 15 sites (VG, VD, VB, XXIVA, IIM, IIC, IIP, XVI.VII, IVF, XXIVB, IIO, XVF, XXIIA, IIK, and seedling area) in KRB. M. pendula habitats in KRB characterized by forest land cover type with temperature of 31.1 ± 0.96 ℃, air humidity of 69 ± 2.73%, light intensity 3183.9 ± 3095 lux, and wind speed 0.7 ± 0.51 m/s.